EFEKTIVITAS MODEL MEA (MEANS ENDS ANALYSIS) TERHADAP KEMAMPUAN MENULIS WACANA ARGUMENTASI MAHASISWA PENDIDIKAN BAHASA DAN SASTRA INDONESIA UNIVERSITAS MUHAMMADIYAH MAKASSAR - Ningsih Wahyu; Rosmini Madeamin (Jurnal Pendidikan Sang Surya, 2024)
The objectives to be achieved in this research are: (1) to determine the ability to write argumentative discourse of Indonesian Language and Literature Education Students at Muhammadiyah University of Makassar without using the MEA (Means Ends Analysis) model in the control class, (2) to determine the ability to write argumentative discourse of Language Education Students and Indonesian Literature at the Muhammadiyah University of Makassar using the MEA (Means Ends Analysis) model in the experimental class, and (3) proving the effectiveness of the MEA (Means Ends Analysis) model for the ability to write argumentative discourse of Indonesian Language and Literature Education Students at the Muhammadiyah University of Makassar. This research is experimental research with a true experimental design model in the form of a posttest-only control design. This model uses an experimental class and a control class, the sampling technique is carried out randomly. To obtain data in this research, instruments were used, namely observation and tests. Observations were carried out in order to obtain an overview and initial conditions of learning to write argumentative discourse. Meanwhile, the test technique is writing argumentation discourse. Data analysis techniques using descriptive statistical analysis and inferential statistics on the SPSS 22.0 for Windows computer program.